MicroRNA-494 Regulates Endoplasmic Reticulum Stress in Endothelial Cells - Chatterjee, Namita; Fraile-Bethencourt, Eugenia; Baris, Adrian; Espinosa-Diez, Cristina; Anand, Sudarshan (Frontiers in Cell and Developmental Biology, 2021)
Defects in stress responses are important contributors in many chronic conditions including cancer, cardiovascular disease, diabetes, and obesity-driven pathologies like non-alcoholic steatohepatitis (NASH). Specifically, endoplasmic reticulum (ER) stress is linked with these pathologies and control of ER stress can ameliorate tissue damage. MicroRNAs have a critical role in regulating diverse stress responses including ER stress. Here we show that miR-494 plays a functional role during ER stress. Pharmacological ER stress inducers (tunicamycin & thapsigargin) and hyperglycemia robustly increase the expression of miR-494 in vitro. ATF6 impacts the primary miR-494 transcript whereas all three ER stress pathways are necessary for the increase in mature miR-494. Surprisingly, miR-494 pretreatment dampens the induction and magnitude of ER stress in response to tunicamycin in endothelial cells and increases cell viability. Conversely, inhibition of miR-494 increases ER stress de novo and amplifies the effects of ER stress inducers. Using Mass Spectrometry (TMT-MS) we identified 23 proteins that are downregulated by both tunicamycin and miR-494 in cultured human umbilical vein endothelial cells. Among these, we found 6 transcripts which harbor a putative miR-494 binding site. We validated the anti-apoptotic gene BIRC5 (survivin) and GINS4 as targets of miR-494 during ER stress. In summary, our data indicates that ER stress driven miR-494 may act in a feedback inhibitory loop to dampen downstream ER stress signaling.